Dissolved Pb and Pb isotopes in the North Atlantic from the GEOVIDE transect (GEOTRACES GA-01) and their decadal evolution - C. M. Zurbrick; E. A. Boyle; R. J. Kayser; M. K. Reuer; J. Wu; J. Wu; H. Planquette; R. Shelley; R. Shelley; J. Boutorh; M. Cheize; L. Contreira; et al. (Biogeosciences, 2018)
During the 2014 GEOVIDE transect, seawater samples were collected for dissolved Pb and Pb isotope analysis. These samples provide a high-resolution <q>snapshot</q> of the source regions for the present Pb distribution in the North Atlantic Ocean. Some of these stations were previously occupied for Pb from as early as 1981, and we compare the 2014 data with these older data, some of which are reported here for the first time. Lead concentrations were highest in subsurface Mediterranean Water (MW) near the coast of Portugal, which agrees well with other recent observations by the US GEOTRACES program (Noble et al., 2015). The recently formed Labrador Sea Water (LSW) between Greenland and Nova Scotia is much lower in Pb concentration than the older LSW found in the West European Basin due to decreases in Pb emissions into the atmosphere during the past 20 years. Comparison of North Atlantic data from 1989 to 2014 shows decreasing Pb concentrations consistent with decreased anthropogenic inputs, active scavenging, and advection/convection. Although the isotopic composition of northern North Atlantic seawater appears more homogenous compared to previous decades, a clear spatiotemporal trend in isotope ratios is evident over the past 15 years and implies that small changes to atmospheric Pb emissions continue. Emissions data indicate that the relative proportions of US and European Pb sources to the ocean have been relatively uniform during the past 2 decades, while aerosol data may suggest a greater relative proportion of natural mineral Pb. Using our measurements in conjunction with emissions inventories, we support the findings of previous atmospheric analyses that a significant portion of the Pb deposited to the ocean in 2014 was natural, although it is obscured by the much greater solubility of anthropogenic aerosols over natural ones.